English as a Commodity: Linguistic Capitalism in Bangladesh’s Private Tutoring and Coaching Centers - Naiem, Al Amin; Thaniyatul Jannath, Samira; K M Asif Iqbal, Akash; Apu Chandra, Karmaker; Khan Sarfaraz, Ali (INTI International University, 2025)
This paper explores the commodification of English in the case of the Bangladesh-based private tutoring centers, where English is being sold as a means of socioeconomic mobility and career success. Through qualitative interviews with coaching center owners, teachers, and parents, the study addresses how English as an asset is published and how tutoring supports the social disparities. Results indicate that English proficiency is regarded as a symbolic and economic capital that opens opportunities to some individuals and denies others. The paper has emphasized the effect of linguistic capitalism on education and provided perspectives on minimizing inequalities in language education.